Experiences of internal and hybrid employee assistance program managers: Factors associated with successful, at-risk, and eliminated programs. (2nd January 2018) - Frey, Jodi Jacobson; Pompe, John; Sharar, David; Imboden, Rachel; Bloom, Lauren
ABSTRACT: Employee Assistance Programs (EAPs) originated as workplace-focused programs delivered largely by peer employees. Over the past 25 years, the once standard internal EAP has largely been replaced by internal/external hybrid programs or outsourced EAP vendors. Many long-standing internal programs have been downsized or eliminated, along with their internal program manager positions. This qualitative study examined the organizational, leadership, and programmatic characteristics associated with the internal and internal/hybrid EAPs from the perspectives of EAP managers working in programs that have thrived and those that have depreciated. Twenty-four current and former internal or internal/hybrid EAP managers were interviewed using a semistructured interview schedule. Qualitative methods were used to identify patterns and themes within the data to describe the experience of internal and internal/hybrid EAP managers and the critical success and risk factors associated with their positions and programs. Five final themes, with 15 subthemes emerged from the data, suggesting that both individual and organizational characteristics of EAP internal and hybrid programs are important to the program's sustainability. These findings offer insights regarding best practices and critical success factors to EAP professionals, EAP purchasers, and the EAP industry.